20 October, 22:15

# For which function is f (x) equal to f^-1 (x) ?f (x) = x+6x-6f (x) = x+2/x-2f (x) = x+1/x-1f (x) = x+5/x-5

+2
Answers (1)
1. 20 October, 23:28
0
We will find the inverse of the given functions:

y = x + 2 / x-2

(x-2) y = x + 2

-2y + xy = x + 2

-2y + xy = x + 2

x (y - 1) = 2 + 2y

x (y - 1) = 2 (y + 1)

x = 2 (y + 1) / (y - 1)

f (x) ^ - 1 = 2 (x + 1) / (x - 1)

The inverse is different.

f (x) = x + 1 / x-1

y = x + 1 / x-1

(x-1) y = x + 1

-y + xy = x + 1

x (y - 1) = 1 + y

x (y - 1) = (y + 1)

x = (y + 1) / (y - 1)

f (x) ^ - 1 = (x + 1) / (x - 1)

The inverse is the same.

Answer:

f (x) = x + 1 / x-1

f (x) ^ - 1 = (x + 1) / (x - 1)

f (x) = f (x) ^ - 1
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍 “For which function is f (x) equal to f^-1 (x) ? f (x) = x+6x-6 f (x) = x+2/x-2 f (x) = x+1/x-1 f (x) = x+5/x-5 ...” in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.